Preconception contraceptive use and miscarriage: prospective cohort study - Elizabeth E Hatch; Lauren A Wise; Kenneth J Rothman; Sonia Hernandez-Diaz; Jennifer J Yland; Amelia K Wesselink; Wendy Kuohung; Krista Huybrechts; Tanran R Wang; David Savitz (BMJ Medicine)
Objectives To evaluate the association between preconception contraceptive use and miscarriage.Design Prospective cohort study.Setting Residents of the United States of America or Canada, recruited from 2013 until the end of 2022.Participants 13 460 female identified participants aged 21-45 years who were planning a pregnancy were included, of whom 8899 conceived. Participants reported data for contraceptive history, early pregnancy, miscarriage, and potential confounders during preconception and pregnancy.Main outcome measure Miscarriage, defined as pregnancy loss before 20 weeks of gestation.Results Preconception use of combined and progestin-only oral contraceptives, hormonal intrauterine devices, copper intrauterine devices, rings, implants, or natural methods was not associated with miscarriage compared with use of barrier methods. Participants who most recently used patch (incidence rate ratios 1.34 (95% confidence interval 0.81 to 2.21)) or injectable contraceptives (1.44 (0.99 to 2.12)) had higher rates of miscarriage compared with recent users of barrier methods, although results were imprecise due to the small numbers of participants who used patch and injectable contraceptives.Conclusions Use of most contraceptives before conception was not appreciably associated with miscarriage rate. Individuals who used patch and injectable contraceptives had higher rates of miscarriage relative to users of barrier methods, although these results were imprecise and residual confounding was possible.